Screening And Growth Patterns Of Chitinolytic Bacteria From The Shells Of Crab (Portunus pelagicus) - Sudin, Sudin; Sulistijowati, Rieny; Hermain, Rita Marsuci (Universitas Negeri Gorontalo, 2020)
Screening of chitinolytic bacteria from crab shells (Portunus pelagicus) was carried out. This study aims to obtain chitinolytic bacterial isolates, determine the zone of chitinase activity qualitative produced and growth pattern by chitinolytic bacteria from crab shells (Portunus pelagicus). The research method used is descriptive research method. This study consisted of 3 stages, namely screening for chitinolytic bacteria (isolation and macroscopic and microscopic identification), determination of the zone of chitinase activity qualitative and growth curve produced by chitinolytic bacteria. Chitinolytic bacterial isolates that were successfully grown, obtained the highest chitinolytic index of 1. Macroscopic and microscopic identification results showed that chitinolytic bacterial isolates were gram-negative rod-shaped bacteria. Logaritmic gowth at 2nd to tenth hours incubation.